Desert Truffles Phylogeny, Physiology, Distribution and Domestication - Kagan-Zur, Varda; Roth-Bejerano, Nurit; Sitrit, Yaron; Morte, Asunción (Soil Biology, 2014)
Desert truffles are found in every known desert, irrespective of the habitat - cool or hot, loamy or acidic, sandy or heavy soil - the only common condition seems to be a limited supply of water. In contrast to 'true' truffles, desert truffles have evolved over time in different families, mainly within the order Pezizales. While in some arid areas, desert truffles have been traditionally used as food, in most regions interest has only recently been increasing, and truffles are now treasured for their nutritional value, as an income source and for research. This volume gives a comprehensive overview of the phylogeny, biology, mycorrhizal association, and distribution of desert truffles, their use, biochemical and medicinal properties, as well as their domestication and cultivation.